Une agronomie pour le XXIe siècle - Richard, Guy; Stengel, Pierre; Lemaire , Gilles; Cellier , Pierre; Valceschini , Egizio (éditions Quae, 2018)
The challenge for agricultural systems today is to produce whilst drastically reducing greenhouse gas emissions, in limited agricultural spaces where the biodiversity, quality of resources, soils, water, air, etc. all have to be protected. This collective work, published to mark the twentieth anniversary of the creation of the Inra Environment and Agronomy Department, takes stock of progress made in this area.